IMPLEMENTING READING STORIES TO TEACH READING TO CHILDREN - Nisa Septiani Mutia; Dameria Magdalena Sidabalok (LINGUISTIKA, 2017)
This research is based on the researcher’s pre-survey on the implementation of reading stories towards children. Young children have an extraordinary ability to record what they have heard. The purpose is also to increase their intelligence and to prepare the children for language learning before they are ready to study at school. During the reading activity, the mothers do not force the children to do any activity. They just observed the children’s development while reading activities and help them increase their language acquisition. The aims of this research are to see the children’s language acquisition process, to identify how storybook is being read by the parents, and also to know the advantages of reading story to young children. Language development is one of the indicators of overall development for children's cognitive ability related to their success in their study. The result showed that reading stories to children can help parents to prepare their children before they are ready to study at school. Reading story to children with bilingual books also increases children’s language acquisition because during the reading activity they got some new vocabularies related to the story. The result showed that the children have different methods and strategies in learning from the story. During the reading process, the mother gives some definition related to the story and read with clear intonation and gestures.